SPIDERS COLLECTED IN RESIDENCES FROM MUNICIPALITIES OF BARBALHA, CRATO AND JUAZEIRO DO NORTE, CE, BRAZIL. - Azevedo, Raul; Silva, Larissa Nascimento; Silva Júnior, Francisco Bento; Azevedo, Francisco Roberto de; Carvalho Júnior, José Moacir De Araújo; Sobreira, Joseph Arimatéias Diniz de Carvalho (Boletín de la Sociedad Zoológica del Uruguay, 2019)
The present work reports the fauna of spiders collected in residences of the municipalities of Barbalha, Crato and Juazeiro do Norte. Ten random neighborhoods were selected in each municipality, including central and border neighborhoods. In each neighborhood, 10 houses were randomly selected, totalzing 30 neighborhoods and 300 houses surveyed. Manual collections were carried out in the interior and exterior of the residences, without replication during the months. Pholcidae was the richest family (S=3). Smeringopus pallidus was the unique species which occurred in all municipalities sampled. Pholcidae are the most abundant family inside residences due an increase of environmental impacts near to Araripe Plateau, species like Sicarius cariri and Leprolochus oeiras can be found inside residences by the first time.